The Future of Museum Studies with Dr. Nicholaus Pumphrey. (12th August 2021) - Welch, Emma
Abstract : "The Profession" opens a window onto the myriad ways scholars have made use of their training in and beyond the academy. In this issue, editorial assistant Emma Welch speaks with Dr. Nicholaus Pumphrey—curator of the Quayle Bible Collection at Baker University—looking into the discourse on museums and archives and the questions it brings for the scholar of religion. What follows is an introduction to the Quayle Bible Collection and its artifacts, plus what the students and staff of Baker University have to say about the future of museum studies as it pertains to the study of religion.